(NfIZI^ESKIE OSNOWY TWERDOTELXNOJ \LEKTRONIKI (B:s (Nu^EBNOE POSOBIE (B/s - (NgUSEWA(B, (NmALXWINA bORISOWNA(B.s; (NdUBININA(B, (NeLENA mIHAJLOWNAs ((NmOSKWA (B:s (Nmgu(B,s, 1986)
(NbIBLIOGR(B.: (NS(B. 310-312s
Keywords: (NfIZI^ESKOE STROENIE MATERIIs; (NmIKRO\LEKTRONIKAs